New approaches on the importance of fatty acids in poultry meat on human health - Saadoun, Ali (Cuban Journal of Agricultural Science, 2014)
Poultry meat is greatly consumed throughout the world, including Latin America. Poultry meat shows very interesting nutritional qualities for human health. Its fatty acid composition is considered favorable for fighting against cardiovascular diseases. Also it can be modified through the diet by including healthy fatty acids, such as EPA and DHA. Key words: fatty acids, poultry meat